Под знаком розы и креста: повесть / В. Кузьмин - Кузьмин Владимир (Приключения Даши Бестужевой, 2012)
Экземпляры: ДБ (20120626) / Инвентарный номер: 43966 / Цена: 232.27 / Авт.знак: К 89 / ББК: 84(2Рос=Рус)6